2016
DOI: 10.1145/2950040
|View full text |Cite
|
Sign up to set email alerts
|

Interactive visualization of 3d scanned mummies at public venues

Abstract: BY COMBINING VISUALIZATION techniques with interactive multi-touch tables and intuitive user interfaces, visitors to museums and science centers can conduct self-guided tours of large volumetric image data. In an interactive learning experience, visitors become the explorers of otherwise invisible interiors of unique artifacts and subjects. Here, we take as our starting point the state of the art in scanning technologies, then discuss the latest research on high-quality interactive volume rendering and how it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Recent advances in graphics hardware and processing power in consumer hardware has enabled a broad use of actual scientific data in applications aimed for science communication for the public at science centers and elsewhere. One such story is presented by Ynnerman et al [62]. The ability of providing the same data as scientists have used in their explorations to the layman user is currently a major change and a paradigm shift in science communication.…”
Section: Related Workmentioning
confidence: 99%
“…Recent advances in graphics hardware and processing power in consumer hardware has enabled a broad use of actual scientific data in applications aimed for science communication for the public at science centers and elsewhere. One such story is presented by Ynnerman et al [62]. The ability of providing the same data as scientists have used in their explorations to the layman user is currently a major change and a paradigm shift in science communication.…”
Section: Related Workmentioning
confidence: 99%
“…Introduction 3D digital data have been rapidly incorporated in archaeological and anthropological fields, and they are providing new and unlimited access to fragile and valuable remains. For instance, 3D digitisations can be used for facial reconstructions such as Robert the Bruce (Wilkinson et al 2017), the creation of interactive virtual displays such as the Gebelein Man at the British Museum (Ynnerman et al 2016), or 3D printed to reveal otherwise hidden trauma such as the Jericho skull (Hirst 2017). Additionally, 3D digitisations allow for more advanced statistical analysis of biological shapes, and the most commonly employed method in anthropology and archaeology is 3D geometric morphometrics.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…For instance, resulting data can be used to create highly detailed records of museum objects (Ahmon 2004;Fontana et al 2002), as demonstrated by projects such as the Virtual Curation Laboratory (Huber 2014;Means et al 2013), as well as allowing digital preservation of fragile material (Means et al 2013;Simon et al 2009) and minimising the damage caused by repeated sampling and handling (Bowron 2003). These records can be used to create virtual exhibitions, both within museums and online (Keklikoglou et al 2016;Means et al 2013;Tucci et al 2011;Ynnerman et al 2016), which will increase public engagement and accessibility of anthropology and archaeology in an increasingly digital age.…”
Section: Accessibilitymentioning
confidence: 99%